PENERAPAN STRATEGI PETA KONSEP UNTUK MENINGKATKAN PRESTASI BELAJAR EKONOMI SISWA KELAS X IPS 1 SMA DWIJENDRA BUALU TAHUN PELAJARAN 2018/2019 - Murniasih, Ni Nyoman; Narayana, I Wayan Widhi Yasa (LPPM IKIP PGRI Bali, 2019)
Concept Map Strategy Can Improve Learning Achievement. This type of research uses a classroom action research approach. The subjects of this study were IPS 1 X grade students of Dwijendra Bualu High School in academic year of 2018/2019 which is consisted of 32 students. The object of research is the application of the Concept Map strategy and learning achievement. Data collection techniques are observation method, test method, and documentation method. The results showed the achievement of KKM students of class X IPS 1 SMA Dwijendra Bualu at initial reflection was 21.875%, Cycle I was 43.75% and cycle II was 100%. The average percentage of student activity in cycle I was 38.23% to 50.50%. Absorption of initial reflection is 52%, cycle I is 62% and cycle II is 77%. The concept map strategy can also increase students' calcical completeness on the initial reflection of 21.875%, in the first cycle 43.75% and cycle II 100%. The Application of Concept Map Strategies can Improve Learning Achievement.